The U.S. Drug Policy Landscape Insights and Opportunities for Improving the View - Kilmer, Beau (RAND Corporation, 2012)
Discussions about reducing the harms associated with drug use and antidrug policies are often politicized, infused with questionable data, and unproductive. This paper provides a nonpartisan primer on drug use and drug policy in the United States. It aims to bring those new to drug policy up to speed and provide ideas to researchers and potential research funders about how they could make strong contributions to the field.